FREQUENCY OF IL 12B GENE POLYMORPHISM AMONG PATIENTS WITH CHRONIC RHINOSINUSITIS POLYPOSIS - Ulugbek S. Khasanov; Ulugbek N. Vokhidov; Jamolbek A. Djuraev (Central Asian Journal of Medicine, 2023)
Analyzing the prevalence of genotypic variants of this polymorphism, we revealed a direct association of the C/C monogenotype of the A1188C rs3212227 polymorphism in the IL12B gene with the development of polyposis processes. In addition, these data emphasize the prognostic significance of the C/C genotype of the rs1800896 polymorphism of the IL-12B gene in the development of CPMS. In carriers of this genotype, the relative risk of developing CPMS increases by more than 3 times, compared with carriers of other genotypic variants of the rs3212227 polymorphism of the IL12B gene.